The Relationship between the Church and Soviet Regime in Lithuania, Latvia and Estonia in 1940–1990. Similarities and Differences - Streikus, Arūnas (Genocidas ir rezistencija, 2002)
Although all Baltic States encountered the same forms of Soviet violence from 1940 to 1990, the reaction of their societies was different. This article discusses how the Soviet regime succeeded in its rules of enforcing and controlling the biggest confessions in the Baltic states with various positions in the society. More advanced secularization of Lutheran confession, departure of most part of clergy and church hierarchy to the West in 1944–1945 and different internal organization determined easier limitation of the Lutheran Church’s internal autonomy in Latvia and Estonia by the Soviet regime. Although the Catholic Church in Lithuania and Latvia formally also had to obey Soviet rules until the beginning of the sixth decade, it was more problematic to the regime than the Lutherans. Because of that the Catholic Church relatively suffered more from the new anti- religious campaign which stared at the end of the sixth decade.